Heterozygous p53-R280T Mutation Enhances the Oncogenicity of NPC Cells Through Activating PI3K-Akt Signaling Pathway - Qin, Zhen-Qi; Li, Qi-Guang; Yi, Hong; Lu, Shan-Shan; Huang, Wei; Rong, Zhuo-Xian; Tang, Yao-Yun; Xiao, Zhi-Qiang (Frontiers in Oncology, 2020)
A heterozygous point mutation of p53 gene at codon 280 from AGA to ACA (R280T) frequently occurs in nasopharyngeal carcinoma (NPC) cell lines, and about 10% NPC tissues. However, the role of this mutation in the pathogenesis of NPC remains unclear. In this study, we generated p53 knockout (KO) NPC cell lines from CNE2 cells carrying heterozygous p53 R280T (p53-R280T) mutation and C666-1 cells carrying wild-type p53 by CRISPR-Cas9 gene editing system, and found that KO of heterozygous p53-R280T significantly decreased NPC cell proliferation and increased NPC cell apoptosis, whereas KO of wild-type p53 had opposite effects on NPC cell proliferation and apoptosis. Moreover, KO of heterozygous p53-R280T inhibited the anchorage-independent growth and in vivo tumorigenicity of NPC cells. mRNA sequencing of heterozygous p53-R280T KO and control CNE2 cells revealed that heterozygous p53-R280T mutation activated PI3K-Akt signaling pathway. Moreover, blocking of PI3K-Akt signaling pathway abolished heterozygous p53-R280T mutation-promoting NPC cell proliferation and survival. Our data indicate that p53 with heterozygous R280T mutation functions as an oncogene, and promotes the oncogenicity of NPC cells by activating PI3K-Akt signaling pathway.